PENGARUH TINGKAT HUTANG, ARUS KAS DAN AKRUAL TERHADAP PERSISTENSI LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan yang Terdaftar di BEI Tahun 2011-2015) - Linawati Linawati (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
Abstract The purpose of this study was to examine the influence of leverage, cash flow operation and accrual to earning persistene moderated good corporate governance. This study used multiple regression methode. Samples are companies listed on the Jakarta Stock Exchange by taking a sample of 42 Manufacturing Companiesfrom 2011-2015. Sampling is done by using purposive sampling method. Test the above hypothesis used SPSS 21. The result of this research explained that the leverage negative significant affect on earning persistence, cash flow positive significant affect on earning persistence,and accrual has not negative affect onearning persistence.While the test resulted from Multipled Regresion Analysis methode showed that corporate governance is not moderation the effect of leverage, cahsflow, and accrual to earning persistence.                                                                                                                         Keywords: earning persistence, leverage, cash flow, accrual corporate governance